The Influence of Service Quality and Brand Image on Customer Satisfaction (Case Study at Bankaltimtara) - RESLIANTY RACHIM; ZULKIFLI ZULKIFLI (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2019)
The purpose of this study was to determine the effect of service quality and image on customer satisfaction on Bankaltimtara, both partially and simultaneously using the study population, namely Bankaltimtara customers who came to the office when the researchers conducted field research. And the sample used in this study amounted to 100 people. The sampling technique in this study uses accidental sampling technique, which is a sampling technique based on coincidence, where the customer meets the researcher by chance. Data collection techniques used in this study are library research and field work research in the form of observations, interviews and questionnaires. This research method is descriptive using validity test analysis tools, reliability test, multiple linear regression analysis, Pearson correlation coefficient test, coefficient of determination test, T test and F test with the help of SPSS software version 23 to determine the effect of each variable. From the results of the analysis, it is known that the value of variable X1 is service quality, variable X2 is brand image and variable Y is customer satisfaction is significantly positive. The statistical test results partially stated that the service quality variable had a significant positive effect on customer satisfaction variables of 32.19% and the brand image variable had a significant positive effect on customer satisfaction variables of 28.86%. While the results of simultaneous testing stated that the variable service quality and brand image variables have a significant positive effect on customer satisfaction variables of 57.13%.